Israeli Students' Evaluations Regarding Leadership Education in Post-Primary Schools - Shenhav Perets; Nitza Davidovitch; Eyal Lewin (MDPI AG, 2023)
This article examines the way students attending middle and high schools in Israel evaluate leadership education in their schools and the extent to which it contributes to their leader self-efficacy. Based on 376 questionnaires completed by teenage girls (n = 243) and boys (n = 133) who attend middle and high school in the public education system in Israel, it focuses on their perceptions regarding their school as their main leadership development establishment. Using a Likert scale to measure attitudes and perceptions of youth leadership, the questionnaire was used to investigate the following topics: the school's efforts to impart leadership and encourage leadership and leadership ability, their self-perceptions of leadership ability, and the impact of the school staff on their leadership development. Students expressed discontent with the school's ability to impart and motivate leadership, and family members and youth organizations are perceived as more influential. Students in middle schools participate more in leadership programs but evaluate the school's contribution to leadership development less favorably than high school students. Although girls and boys are participating in leadership programs at a similar rate, girls' leader self-efficacy is relatively low. Implementing leadership education has some deficiencies that require policymakers to make necessary adjustments regarding age and gender.